Adapting to climate change - Huddleston, Emma (Climate change (Core Library (Firm)), 2021)
Explores the things people can do to adapt to climate change, and examines the causes of climate change. Profiles climate activists and scientists. Includes color photographs, infographics, sidebars, a glossary, and additional resources.